APLIKASI LAUDRY MENGGUNAKAN SMS GATEWAY - Ainulyaqin, Mohammad Syawal; Snae, Menhya (Jurnal Teknologi Terpadu, 2018)
Laundry is a process of washing textile materials using water, washing machines, and detergents. Currently Laundry business is one of the sectors of small and medium enterprises which is rapidly developed. Nowadays, lifestyle and level of human mobility needs higher efficiency in washing and ironing clothes clean and tidy it requires expertise. This would not be possible by a busy person in his daily life. To answer this challenge, laundry business becomes the solution. Gajayana Laundry is one of the laundry business which is located at Ahmad Yani street. Currently Gajayana Laundry still apply a system that is still manual in the laundry service process by making a note receipt laundry. Employee in charge of recording information about the laundry received by writing manual or handwriting, in addition to errors due to recording information the number of laundry clothes that resulted in the loss of one of the clothing belonging to the customer, the uniformity of the letter in the laundry archive books that can confused the employees and the difficulties of the spread information to customers such as holiday information, information informing that the customer's laundry has been completed, and information price changes that certainly in the absence of such information may cause a sense of disappointment from the customers. The results of this study can be concluded that the creation of a laundry application using SMS Gateway and apply these applications to help parties Gajayana Laundry in the laundryservice and the dissemination of information. The research method used is descriptive method and data collection technique used in this research are interview, literature study, observation and questionnaire. Making this application using Visual Basic 2010 programming language andMySQL database.